Teaching the Science of Human Flourishing, Unlocking Connection, Positivity, and Resilience for the Greater Good - Eve Ekman PhD; Emiliana Simon-Thomas PhD (SAGE Publishing, 2021)
Background Human flourishing is a long sought-after aspiration historically considered and espoused through religious, philosophical, and creative avenues. Only recently has western science began to investigate the meaning, underlying foundations of, and effective strategies for promoting flourishing in life. Objective Here, we present a framework for teaching the science and practice of human flourishing grounded in connection, positivity, and resilience (CPR) based on a synthesis of theoretical frameworks and observations and input from a global sample of learners enrolled in an online course. Methods The CPR framework is distilled from empirical research in psychology and neuroscience and an applied pedagogy of flourishing delivered through a massive open online course (MOOC) that has reached over 650,000 people worldwide. Results Building knowledge and skills tied to three pillars of CPR: connection, positivity, and resilience intrinsically and measurably reinforces the experiences and behaviors that foster flourishing, mainly through prosocial human connection. Conclusion Human flourishing is malleable and the CPR framework is a promising method for teaching people the key ideas, spaces of opportunity for change, and behaviors, activities, exercises, and practices that strengthen flourishing in life.